Comparative Study on NACA-9405, NACA-9503 and NACA-9506 Airfoil Profiled Blade Open-Channel Flow Cross-Flow Turbine - Prakoso, Aji Putro; Piseno, Wirawan; Bisono, Damawidjaya; Saefudin, Deny Bayu; Fudholi, Ahmad; Rohman, Fikri Nur (Institute of Research and Publication Indonesia (IRPI)., 2023)
Several agricultural areas in Indonesia are classified as underdeveloped rural areas, and challenging to acquire electricity from the primary grid. On the other hand, some pico hydropower potentials can be found in agriculture, especially at the irrigation dam spillway flows. However, no such technology can convert the energy inside the water open-channel flow through dam spillways into electricity. Crossflow turbines (CFT) are expected to utilize dam spillways’ power due to their ability to convert the kinetic energy of water. Prior studies found that airfoil profile could slightly increase CFT efficiency and affect the interaction between water and turbine. Using planar two-dimensional computational fluid dynamics (CFD) numerical simulation analysis, the current study investigated the energy conversion phenomenon inside different open-channel CFT blade profiles. This study simulates CFT working at 3 meters of total head and 0.04 m3/s of water discharge put into the dam spillway’s downstream. The turbine blade profiled with the National Advisory Committee of Aeronautics (NACA) standard airfoil numbered 9405, 9503, and 9506 are being compared and investigated in the present study. CFD numerical analysis results show that the forward direction NACA airfoil profiled blades deliver better efficiency than the reversed one. These findings contradict the prior study’s results which tested airfoil profiled CFT working as usual with nozzle. This phenomenon indicated differences in the energy transfer process between open channel CFT and the ordinary CFT with a nozzle. Furthermore, current work finds that forward NACA-9503 CFT has a higher efficiency than other tested airfoil profiles, with 57.05% efficiency. In addition, the present study finds that the NACA-95XX airfoil has a more suitable chamber curve with the original CFT blade’s curve than the NACA-94XX airfoil by velocity triangle analysis. Then, the NACA-9503 profile is thinner than the NACA-9506 profile, which eases water flowing through the turbine blades.